2015
DOI: 10.1002/ajoc.201500235
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Pharmacologically Active Compounds that Contain a Benzoxazole Scaffold

Abstract: In recenty ears, the emergence of biologically active compounds that contain ah eterocyclic ring has gained ag reat deal of attention among medicinal chemists. Among these, benzoxazole-based compounds are particularly attractive because of their wide range of pharmacological activities. In this focus review, we highlight recent advancements in the development of benzoxazole-based pharmacologically active compounds since the year 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 156 publications
0
34
0
1
Order By: Relevance
“…Over 80 %o fc urrently prescribed small molecule drugs contain aheterocyclic ring. [1] Heterocycles are rigid molecules that can form hydrogen bonds as well as hydrophobic interactions,m oreover they can be modified to adjust lipophilicity,p olarity,a queous solubility,a nd selectivity.O xazoles (and oxazolines) are very common heterocycles and are found isolated or conjugated to aromatic rings,f or example, with benzene,k nown as benzoxazoles.B enzoxazoles are frequently found in pharmaceutically active compounds [2] and natural products for example in plants (neosalvianen, salvianen, and salvianan); [3] marine sponges (nakijinol, [4] pseudopteroxazole, [5] and ileabethoxazole) [6] as well as bacteria (UK-1, [7] caboxamycin, [8] A33853, [9] calcimycin, [10] nataxazole, [11] and AJI956). [12] Benzoxazole compounds are prescribed as anticancers,a nti-inflammatories (flunoxaprofen, [13] benoxaprofen [14] ), antibacterial (calcimycin, [15] boxazomycin [16] ), and muscle relaxant (chlorzoxazone [17] ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 80 %o fc urrently prescribed small molecule drugs contain aheterocyclic ring. [1] Heterocycles are rigid molecules that can form hydrogen bonds as well as hydrophobic interactions,m oreover they can be modified to adjust lipophilicity,p olarity,a queous solubility,a nd selectivity.O xazoles (and oxazolines) are very common heterocycles and are found isolated or conjugated to aromatic rings,f or example, with benzene,k nown as benzoxazoles.B enzoxazoles are frequently found in pharmaceutically active compounds [2] and natural products for example in plants (neosalvianen, salvianen, and salvianan); [3] marine sponges (nakijinol, [4] pseudopteroxazole, [5] and ileabethoxazole) [6] as well as bacteria (UK-1, [7] caboxamycin, [8] A33853, [9] calcimycin, [10] nataxazole, [11] and AJI956). [12] Benzoxazole compounds are prescribed as anticancers,a nti-inflammatories (flunoxaprofen, [13] benoxaprofen [14] ), antibacterial (calcimycin, [15] boxazomycin [16] ), and muscle relaxant (chlorzoxazone [17] ).…”
Section: Introductionmentioning
confidence: 99%
“…[29] The fabrication of novel substituted 5-( [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazol-3-yl)-1,3-benzoxazole derivatives was reported by Janardhan et al (2012) and all of these compounds were screened for their antibacterial activities by the method of cup-plate technique against some of the species of gram positive and gram negative bacteria in comparison to control streptomycin. Investigation revealed that compound 5-(6-phenyl- [1,2,4]triazolo [3,4- 3,4]thiadiazol-3-yl)benzoxazole (18) exhibited promising antibacterial activity against gram positive strains of B subtilis, S aureus with % zone of inhibition 16 and 21 mm, respectively and gram negative strains of E coli and Proteus vulgaris with % zone of inhibition 25 and 30 mm. The rest the compounds showed moderate to low activities.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Though some of compounds showed significant anticancer activity against various cancer cells however, compound (E)-4-(2-(4,5-dimethoxybenzoxazol-2-yl)-2-(3,4,5-trimethoxyphenyl)vinyl)-2-methoxyphenol (47) was found to exhibit higher potency than standard drug etoposide with GI range≤0.1 to 0.13 μM. [50] A facile series of derivatives of novel fused 7-nitro [1,2,4]triazolo [3,4-b] [1,3]benzoxazole-3-thiol were fabricated by Tamaka (2017). The newly synthesized compounds were evaluated by their effect of cyclotoxity on cell lines of peripheral blood mononuclear cells (PBMCs).…”
Section: Anti-cancerous Activitymentioning
confidence: 99%
“…The process in preparative investigations on oxazoles , isoxazoles , oxazolines , isoxazolines , oxazolidines , isoxazolidines , oxazolones , isoxazolones , benzoxazoles , and benzisoxazoles has been summarized in exhaustive reviews. Also, the application of most of these heterocyclic scaffolds in medicinal chemistry has been reviewed recently, just to mention the broad pharmacological (e.g., anticancer, antimicrobial, antidiabetic, anti‐inflammatory, and anticonvulsant) activity of benzoxazoles or the specific significance of isoxazoles for neuropsychiatric therapeutics . The only heterocyclic scaffolds, for which so far extensive reviews exist regarding their significance in crop protection chemistry, are pyrazole , thiazole , isothiazole , pyridine , pyridazine , and pyrimidine .…”
Section: Introductionmentioning
confidence: 99%